The Impact of Macro-Economic Factors on Housing Loan Demand in Singapore - Hoang, Phuong Mai (2008)
The research aims to evaluate trends and macro economic factors which have influence in the demand of the housing mortgage loan in Singapore. The study is to provide the insight of demand of housing mortgage loan in Singapore over last thirty years and the conclusively important factors that have highly positive effects on the growth of the market and the potential future for the loan market in Singapore. The study intends to demonstrate that the housing mortgage loan in Singapore is not affected by any single macro factor as many previous researchers have done before; it could be affected by other factors such as the GDP (or GNP), interest rate level, inflation rate, population, income tax (housing tax) and other behavioral factors simultaneously. The investigation on the impacts of various factors at aggregate level as mentioned above will be analyzed using unit root test, Johansen Cointegration and Granger Causality test. The empirical results showed that GDP, Employment (measured by the labor force participation rate) would have positive relationship on the size of housing mortgage loan whereas inflation and SIBOR would give negative relationship on the demand of housing loan in Singapore, either direct or indirect way. From the result of this analysis, it is crucial to find out the most important factors on the development of housing loan in order to enhance further. The government’s housing policies are playing a significant role in determining development of Singapore housing market. At the end, the weakness of this study could become initiative for further investigation on housing mortgage loan at primary and secondary as well as the development of models with other more interesting factors such as behavioral factors in other countries with different economical and social background.